AN ANALYSIS ON ENGLISH STUDENTS’ ABILITY IN TRANSLATING FROM ENGLISH INTO INDONESIAN - Imandari, Ratih Zatil; Suhartono, Luwandi; Wijaya, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to know the students’ ability and the pronoun common  errors made by the students’ in translating from English into Indonesian in sixth semester students at English Education Study Program of Tanjungpura University in academic year 2014/2015 who has passed the translation subject. The method used in this research is the descriptive qualitative method which is to find deeper understanding toward the research purposes.  The study sample are 23 students who produced 23 translation products, the data analysis applied is descriptive analysis which involves coding, analyzing and summarizing. The result of the study shows that the students’ ability in translating from English into Indonesian generally is Excellent, with 15(65.2%) students achieved excellent level and 8(34.8%) students achieved good level. Furthermore, for the pronoun common errors made by the students in translating from English into Indonesian are the students did not mention or omitted the pronoun in the target text.   Key words : Translation, Pronouns, Students’ Ability Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan dan kesalahan umum kata ganti yang dibuat oleh mahasiswa dalam menerjemahkan dari bahasa Inggris ke bahasa Indonesia pada mahasiswa semester enam Program Studi Pendidikan Bahasa Inggris Universitas Tanjungpura di tahun akademik 2014/2015 yang telah lulus mata kuliah Translation. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif yaitu untuk menemukan pemahaman yang lebih dalam terhadap tujuan penelitian tersebut. Sampel penelitian adalah 23 mahasiswa yang menghasilkan 23 produk terjemahan, analisis data yang digunakan adalah analisis deskriptif yang melibatkan menandai, menganalisis dan meringkas. Hasil penelitian menunjukkan bahwa kemampuan mahasiswa dalam menerjemahkan dari bahasa Inggris ke bahasa Indonesia umumnya sangat baik, dengan 15 (65,2%) mahasiswa mencapai tingkat yang sangat baik dan 8 (34,8%) mahasiswa mencapai tingkat yang baik. Selanjutnya, untuk kesalahan umum kata ganti yang dibuat oleh mahasiswa dalam menerjemahkan dari bahasa Inggris ke bahasa Indonesia adalah mahasiswa tidak menyebutkan atau menghilangkan kata ganti dalam teks sasaran.   Kata Kunci : Terjemahan, Kata Ganti, Kemampuan Siswa